Monetary and Fiscal Policies in Brazil and the behavioral approach under the inflation-targeting regime - Freitas, Raphael José Pereira (2025)
Tese (doutorado)—Universidade de Brasília, Faculdade de Administração, Contabilidade, Economia e Gestão de Políticas Públicas, Departamento de Economia, Brasília, 2025.